The Measurement of Evidence‐Based Healthcare Competence of Nurses and Associated Background Factors: A Scoping Review - Härkonen, Henna; Hannila, Hanna-Maria; Oikarinen, Anne; Kaariainen, Maria; Ylimäki, Saija; Hietaniemi, Anne-Mari; Holopainen, Arja; Jansson, Miia; Polkki, Tarja; Kaakinen, Pirjo; Kanste, Outi; Tuomikoski, Anna-Maria (Wiley, 2026)
Advancing evidence-based practice requires nurses to have competence in the spectrum of evidence-translation process known as evidence-based healthcare. A scoping review was conducted to identify the instruments used to measure nurses evidence-based healthcare competence and map the associated background factors. The review followed the JBI guidelines with a search made to seven databases CINAHL (EBSCO), PubMed, Scopus, Medic and gray literature EBSCO Open Dissertations & MedNar in 2021 and 2023. A total of 52 studies were included. Nurses' evidence-based healthcare competence related areas were measured with various instruments (n = 23). A total of 24 background factors were examined of which the six most frequently examined with reported associations to nurses' evidence-based competence were: educational level, work experience, EBP education, age, clinical setting, and research experience. Future research should examine the relation of measurement instruments to evidence-based healthcare competence, healthcare requirements and nursing roles, with further exploring the significance of background factors.